Profile of Diabetic Foot Ulcer Patients at Tertiary Care Hospital in Surabaya, Indonesia - Arisvia Sukma Hariftyani; Hermina Novida; Mouli Edward (Jurnal Berkala Epidemiologi, 2021)
Background: Diabetic Foot Ulcer (DFU) has been associated with a high mortality rate of Diabetes Mellitus (DM) patients. Both behavioral and biological factors cause predisposition to DFU. Purpose: This research describes the profile of hospitalized DFU patients at a tertiary care hospital in Surabaya. Methods: A retrospective descriptive study that analyzed medical records of hospitalized T2DM patients with DFU in Dr. Soetomo General Hospital. Sampled respondents were patients ≥ 21 years old who were hospitalized between 2016–2018. Demographic data, clinical characteristics, medical histories, length of hospital stay, laboratory results, precipitating factors, microorganism culture results, treatment, and outcome were analyzed. Descriptive analysis is presented in the form of narratives, tables, and diagrams. Results: 9.08% of hospitalized Type 2 DM (T2DM) cases were related to foot ulcers. The average patient age was 57.00 ± 9.83 years with no gender predominance. DM was poorly controlled (Mean HbA1C 9.78±2.83%; RBG 251.83 ± 158.15 mg/dL). The majority of patients had sepsis (68.26%) and renal function impairment (62.72%). Ulcers with Wagner grades of 4–5 were frequent (41.31%). The highest percentage of sepsis (80.49%) and the average leukocyte level (22.60±11.95 x109/L) were found in gangrenous feet. Anemia was more predominant and severe in ulcers with higher Wagner grades. Trauma and Escherichia coli were the most common precipitating factors and microorganisms isolated, respectively. Amputation was performed for 82.36% of patients who were admitted to hospital with gangrene. The Lower Extremity Amputation (LEA) and mortality rates were 14.11% and 40.93%, respectively. Conclusion: DFUs were found to have a relatively high prevalence among T2DM patients, and must never be neglected due to the high associated mortality rate.